STUDIES ON THE ARACEAE OF THE LESSER SUNDA ISLANDS II: NEW RECORD FOR SCINDAPSUS HEDERACEUS MIQ. IN BALI - Ina Erlinawati; Ni Putu Sri Asih; Agung Kuniawan; Yuzammi Yuzammi (BRIN Publishing (Penerbit BRIN), 2019)
ERLINAWATI, I., ASIH, N. P. S., KURNIAWAN, A. & YUZAMMI. 2019. Studies on the Araceae of the Lesser Sunda Islands II: New record for Scindapsus hederaceus Miq. in Bali. Reinwardtia 18(2): 51‒64. — The native Araceae of the Lesser Sunda Islands consists of 19 genera and 33 species, of which Scindapsus hederaceus Miq. is newly reported for Bali. This species distributed from Indo-China to West and Central Malesia. Formerly, in Indonesia the species has been found in Sumatra, Java and Borneo. Short descriptions of all species found in the Lesser Sunda Islands and a key to the genera are provided.